Process Management Why Project Management Fails in Complex Decision Making Processes - de Bruijn, Hans. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
What is it that makes a manager or a politician a successful decision maker? Our first inclination would be to say decisiveness and substance. Many managers who met those criteria, however, have had to abandon the field in the past several years..--The authors of Process Management regard a manager as successful if he pays much attention to the process aspects of change. Successful management depends on the extent to which the 'stakeholders' are involved in the decision making and see their own interests protected. This book offers a wealth of insights about this 'process management'. --The book has been thoroughly revised and updated. It contains a large number of new examples. Risks and shortcomings of process management are explained more accurately. The authors also address strategies to deal with the disadvantages of process management. Moreover, there is an extra emphasis on the role of substance in processes.